The effects of magnesium-containing coatings on the healing of soft tissues surrounding oral titanium abutments: a narrative review - Zheng, Hongya; Shang, Chenxi; Li, Ping; Zhao, Wenjie; Niu, Yumei; Pan, Shuang; Zhang, Shuang (Frontiers in Dental Medicine, 2025)
The inherent limitations of smooth titanium abutments—particularly inadequate soft tissue sealing that predisposes implants to infection and inflammation—underscore the need for surface modifications. This review synthesizes evidence on magnesium-containing coatings as a bioactive solution to enhance peri-implant soft tissue healing. Through 1) modifying the surface properties of the implant abutment to promote better cell adhesion and proliferation; 2) releasing Mg2+ to promote fibroblast migration, collagen synthesis, and angiogenesis; and 3) exerting antimicrobial effects and regulating inflammatory responses, these coatings establish a microenvironment conducive to robust tissue integration. This helps prevent peri-implant infections and inflammation, strengthens soft tissue attachment, and improves the long-term stability of dental implants, providing a new direction for the development of biomedical materials.